Audio Description Practice in the Catalan L1 Classroom: Pedagogical Challenges and Opportunities in a Minoritized Language Setting - Bardini, Floriane; Espasa, Eva (Journal of Audiovisual Translation, 2023)
Audio description (AD) has been successfully used in educational settings, especially in foreign language learning—often in combination with other audiovisual translation modes. Most studies have focused on advanced foreign language learners, in the context of higher education. The use of AD in school settings, and in connection with L1, is a promising but arguably under researched area, which our study explores. The AD workshop conducted in a Catalan secondary school in the realm of the research presented in this article is now part of a forthcoming catalogue of activities to encourage the use of Catalan among students, which is published by the Generalitat de Catalunya and addressed to Catalan schools. The article outlines the pedagogical design of the intervention, its main results, limitations, and ways forward. We report a positive effect of practising AD on students’ lexical and syntactic abilities in Catalan and an important impact on their awareness on blindness and functional diversity, as well as the development of critical thinking and empathy. One of the challenges of the activity was to evaluate students’ productions and another was to deal with multilingualism and translanguaging in the classroom, two key aspects that are also discussed in the article. Lay summary Film audio description is an aural description of what happens on screen inserted between dialogues and important sounds. It is a mode of audiovisual accessibility for persons with blindness or low vision, but we can also use it in education. In this context, students create an audio description as a way of practising their language skills: this is called didactic audio description and it has been used with success in foreign language learning in universities. Our study explores the use of didactic audio description in secondary school and in the local language of instruction (L1). Our project took place in a secondary school in Catalonia. The project involved two researchers (the authors of this article), a professional audio describer, a teacher of Catalan, and 80 students aged 12-13. These students participated in a workshop. The workshop included a presentation of what audio description is, a first practice, and a guided final practice. This final practice consisted in the audio description of a short film where the main character is blind: The Fish and I, by Babak Habibifar (2020). In this article we inform on didactic audio description, we explain the methodology of our study, the realisation of the workshop, and our most important results. These results concern the main benefits of didactic AD in L1 in secondary school. The most important results are: The benefits of didactic AD for developing language skills in L1. The benefits of didactic AD for developing other competences, such as working in team or analysing a film. The benefits of didactic AD for making students aware of blindness and diversity. The benefits of didactic AD for the revitalization of Catalan, a minority language. The article also presents the difficulties that the research team encountered. Some of these difficulties were evaluating the students’ work and dealing with multilingualism in the classroom.